Zinc Deficiency in Men Over 50 and Its Implications in Prostate Disorders - Ann Katrin Sauer (Frontiers in Oncology, 2020)
Research has been consistently showing the role of zinc (Zn) in prostate function. In this article, we review the current literature on the anatomy and main functions of the prostate, highlighting the role of zinc. In particular, we will review the etiology of benign prostate enlargement (BPH), its prevalence in men over 50, the likelihood of BPH becoming prostate cancer (PCa), and explain the relationship of zinc and apoptosis in the prostate cells and the implications for BPH and PCa. We present a model that explains how endogenous factors provoke excretion of zinc or limit zinc absorption, and how exogenous factors like nutrition and drugs regularly used in men over 50 can significantly decrease zinc status and thereby increase the risk of BPH. Finally, we explain how Zn amino acid (AA) complexes may be capable of avoiding antagonists and inhibitors of zinc absorption, thereby increasing the bioavailability of zinc for the necessary biological processes in the prostate.